Relationship Between Anxiety Levels With Hypertension Events In Elderly In Public Healt Ujung Loe - Nirmawati; Adam; Andi Suswani (Comprehensive Health Care, 2019)
Hypertension is an increase in blood pressure> 140/90 mmHg. with increasing age, almost all people experience hypertension. Cases of hypertension that occur at the health center at the end of the street are 78 people who suffer and among them 52 elderly people who suffer from hypertension. The purpose of this study was to determine the relationship between the level of anxiety with the incidence of hypertension in the elderly at Puskesmas Ujung Loe in 2018. Research methods: This study used an analytic observational design with a "cross-sectional" approach. From the results of preliminary studies conducted by researchers on July 2, 2018, with 34 respondents. The measuring instrument used is an observation sheet. Data analysis was used using Fisher's test, a purposive sampling technique. The results of research conducted using the fisher test obtained p-value = 0.034 (p ≤ (α = o, 05), then Ho was rejected and Ha was accepted. So it can be concluded that "There is a relationship between‘ ‘Relationship between Anxiety Levels and Hypertension in the Elderly at Ujung Loe Public Health Center in 2018. It is recommended for families to be able to provide care for the elderly especially to help reduce the risk factors for hypertension in the elderly.